Unraveling Biogeographic Boundaries Within the Sierra Madre Oriental, México: An Endemicity Analysis Using a Taxonomically Diverse Dataset - Irene Goyenechea Mayer‐Goyenechea; Gustavo Montiel‐Canales; Juan Márquez; Claudia T. Hornung‐Leoni; Jesús M. Castillo‐Cerón; Norma L. Manríquez‐Morán (Ecology and Evolution)
ABSTRACT The Sierra Madre Oriental (SMO) is a significant mountain range and one of Mexico's 14 biogeographical provinces. Its delimitation has been debated. This study aims to analyze the distribution of plants, beetles, odonates, amphibians, reptiles, and mammals using an endemicity analysis to identify endemism areas and confirm the SMO's biogeographical units. Georeferenced data for 326 species distributed in the Sierra Madre Oriental were compiled using QGIS software, and an endemicity analysis (EA) was carried out with NDM‐VNDM to evaluate taxon distribution congruence in predefined grids. Different grid sizes and specific parameters were used to identify areas of endemism, with an Endemicity Index (EI) assigned to measure the consistency of these areas. Six main areas of endemism (EA) were identified: two in the northern region and four in the southern region of the SMO. These areas are supported by several taxa, except mammals, which did not significantly contribute to the identified AEs. The study suggests new boundaries within the SMO, establishing the Rio Verde as the natural barrier in the north rather than the Moctezuma River. The multi‐taxonomic analysis supports dividing the SMO into two subprovinces, proposing a new delimitation based on the distribution of species with different dispersal capacities. This new regionalization can be useful for prioritizing conservation areas and designing more effective strategies. Future research should include more distribution data of mammals and birds to strengthen these results and better define the subprovinces and biogeographical districts of the SMO.